Anti-Theft Bike Rack - Shafrizal, Shahirul Haziq; Anuar, Muhammad Aidiel; Anuar Halim, Izzuddin Najmi; Mohammad Noor, Hafsa (Multidisciplinary Applied Research and Innovation, 2022)
Bicycle rack typically consist of a base with supporting rails on the side to fit the tyre of a bicycle. This rack act like a parking lot for bicycle, it is used to store and keep in the bicycle and make sure it will not fall. However, the rack available on the market today are very basic and not very secure. It is the same case for the public bicycle rack which in Malaysia, even a basic bicycle rack is hard to find as people prefer to ride a car or motorcycle. This public bicycle rack mostly can be found near public transportation station. A bicycle rack with built-in lock system was fabricated to enhance the security of the bicycle and will ease the user. The fabrication of anti-theft bike rack consist of stopper, pillar, housing, electronic box, and U-shape lock. The bicycle rack strength has been tested by forcefully pulling the U-shape lock using maximum human effort. The electronic locking system has been tested by attempting a false trials to observe whether it will release the lock or not. The first experiment shows some deformation of the U-shaped lock, but the whole locking structure remain intact. The electronic locking system remain locking the U-shape lock when the PIN number is incorrect. The result from these experiments successfully testify the objective which to enhance the security of the bicycle rack, when the u-shape lock remain locking after have been pulled out and the electronic locking system is fully capable to perform its duty with 0.01% of hacker ability. It can be concluded that the fabrication of this product fulfilled the study objectives. However, there are few improvements that can be considered such as adding more solenoid, hybrid power source, and add cover for the electronic box.